Muscle hypertrophy in cancer patients and survivors via strength training. A meta-analysis and meta-regression. (July 2021) - Koeppel, Maximilian; Mathis, Katlynn; Schmitz, Kathryn H.; Wiskemann, Joachim
Graphical abstract: Highlights: Inactive patients lose muscle mass. Resistance training counteracts impaired anabolic signal pathways. Unsupervised resistance training shows no increase in muscle mass. Expert supervision appears to be crucial to achieve muscle hypertrophy. Abstract: Background: Muscle wasting has a negative effect on treatment toxicity and cancer prognosis. Resistance training appears to be a promising approach to counteract the loss of muscle mass. Methods: Pubmed, Cochrane Library, SportDiscus and CINAHL. Randomized controlled resistance training trials with cancer survivros where eligible if lean body mass (LBM) or muscle mass were assessed. Results: A total of 34 trials were included into the primary analysis. Compared to the control individuals, the intervention groups show a superiority in LBM of 0.85 kg (95 % CI = 0.26–1.43, p = .004). Isolated, the participants in the intervention groups show an increase in LBM of 0.51 kg (95 % CI = −0.05–1.06, p = .072); the control groups displayed a decrease of −0.59 kg (95 % CI= −1.04 to 0.06, p = .078). Supervision displayed an mediating role. Conclusions: Resistance training can counteract the loss of muscle mass in cancer patients. Especially in a supervised setting.